Research on the association of breast cancer patients’ prognosis with internal mammary sentinel lymph node biopsy - JIA Ruijie, SHI Zhiqiang, ZHANG Qi, LU Yongjin, ZHENG Junsheng, SUN Jing, BI Zhao, SUN Xiao, WANG Yongsheng, QIU Pengfei (Zhongguo aizheng zazhi)
Background and purpose: Internal mammary sentinel lymph node biopsy (IMSLNB) is a minimally invasive diagnostic technique for regional lymph nodes in breast cancer, which can provide accurate lymph staging and guide adjuvant treatment decision, but its clinical application has been controversial. The purpose of this study was to investigate the prognosis of IMSLNB in early breast cancer. Methods: In this study, a retrospective cohort of 7 949 patients with breast cancer from January 1, 2016 to December 31, 2021 was analyzed. After applying propensity score matching, the patients were divided into IMSLNB group and no-IMSLNB group, and the regional recurrence -free survival (RRFS), local recurrence-free survival (LRFS), distant metastasis-free survival (DMFS), disease-free survival (DFS) and overall survival (OS) of the two groups were compared. This study was approved by the Clinical Research Ethics Committee of the Affiliated Tumor Hospital of Shandong First Medical University (approval number: SDTHEC20130324). Results: A total of 990 patients were included in the final analysis (330 in the IMSLNB group and 660 in the no-IMSLNB group). IMSLN metastasis was found in 54 patients in the IMSLNB group, including 47 patients with axillary lymph node (ALN) metastasis and 7 patients with IMSLN metastasis only. The IMSLN transfer rate was 16.4%. The median follow-up of 41 months showed that the IMSLNB group demonstrated better 3-year DFS [98.4% vs 94.2%, hazard ratio (HR)=0.509; 95% CI: 0.312-0.828, P=0.007] and 5-year DFS (92.5% vs 87.3%, HR=0.214, 95% CI: 0.206-0.222, P=0.011) compared with no-IMSLNB group. However, no significant differences were observed in 3-year OS (99.1% vs 99.4%, HR=0.618, 95% CI: 0.231-1.655, P=0.338) or 5-year OS (98.5% vs 99.1%, HR=0.52, 95% CI: 0.51-0.53, P=0.392) between the two groups. The 3-year RRFS in the IMSLNB group was better compared with the no-IMSLNB group (99.09% vs 97.73%, HR=0.066; 95% CI: 0.061-0.071, P=0.048), while no significant differences were observed in 3-year LRFS (99.70% vs 98.19%, HR=0.209; 95% CI: 0.201-0.217, P=0.130) or DMFS (95.76% vs 96.06%, HR=0.865, 95% CI: 0.858-0.872, P=0.820) between the two groups. The exploratory subgroup analysis of DFS revealed that patients in the following subgroups could significantly benefit from IM-SLNB (P<0.05): diagnosis age (≤50 years), premenopausal status, BMI (≤24), lymphovascular invasion (LVI, present), tumor location (lateral), molecular subtype [hormone receptor positive (HR+)/ human epidermal growth factor receptor 2 negative (HER2-)], histological type (invasive ductal carcinoma), and axillary lymph node status (positive). Conclusion: IMSLNB can provide more accurate regional lymph node staging for early breast cancer, help optimize adjuvant radiotherapy strategies, and improve patients’ DFS and RRFS. It can be promoted as a minimally invasive staging technique for regional lymph nodes.